Hudud and Shariah: Politicising Religion in Malaysia - Afiqah Zainal (2017)
The impending Himpunan 355 rally tomorrow (18 February 2017) and the current discourse on hudud in Malaysia exemplifies the effects of religious outbidding between UMNO and PAS on the Muslim populace. To prevent Islam from being cast as a radical ideology, hudud must be contextualised to its past and present.